Treating Facial Scars using Polydioxanone Threads - Mohammad Khaled Hamolaila; Mazen Zenati; Asaad Shehada (JPRAS Open)
Summary: Traditional scar treatments, such as laser therapy, chemical peels, and surgery, are expensive and require long recovery times. Polydioxanone (PDO) threads offer a minimally invasive and cost-effective solution that enhances collagen production and skin texture.This study aimed to evaluate the effectiveness of PDO threads in the management of atrophic facial scars due to the lack of clinical research on this topic.A prospective clinical study was conducted on 20 patients with facial atrophic scars caused by accidents or previous surgical procedures. The patient and observer scar assessment scale was used to evaluate the scars from the observer's and patient's perspectives at three-time points for each patient. The observer assessment included the following variables: vascularity, pigmentation, thickness, pliability, surface area, and homogeneity. The patient assessment included the following variables: pain, color, stiffness, thickness, appearance, and itching.Statistically significant improvement was observed in atrophic facial scars treated using PDO threads in all observer variables (p<0.001). Significant improvement was recorded in the patient's color, stiffness, thickness, and appearance variables; however, itching sensation increased between T0 and T1 with no statistically significant differences in the pain variable.Within the limits of this study, we conclude that PDO threads are known for ease of use, availability, and biocompatibility. They biodegrade naturally, reducing irritation risk. By stimulating collagen, PDO threads promote natural skin regeneration and thereby improve scars without using foreign materials. The treatment method is safe and minimally invasive, with short recovery times. Clinical studies showed significant improvements in atrophic facial scars with high patient satisfaction.